2015
DOI: 10.1007/s12035-015-9111-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway

Abstract: In this study, we investigated the neuroprotective effect of sevoflurane against ischemic brain injury and its underlying molecular mechanisms. Transient global brain ischemia was induced by 4-vessel occlusion in adult male Sprague-Dawley rats. The rats were pretreated with sevoflurane alone or sevoflurane combined with LY294002/wortmannin (selective inhibitor of PI3K) before ischemia. Cresyl violet staining was used to examine the survival of hippocampal CA1 pyramidal neurons. Immunoblotting and immunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…Caspase-3 is responsible for DNA fragmentation and plays a critical role in apoptosis (McIlwain et al, 2015; Sun et al, 2015). Recently, several researchers have suggested ischemia/reperfusion-induced brain injury might be ameliorated by inhibiting caspase-3 signaling (Wen et al, 2016;Yang et al, 2015a), and in the present study, glycyrrhizinwas found to inhibit increase in caspase-3 and -9 levelscaused by MCAO-induced brain damage (Figure 4).…”
Section: Discussionsupporting
confidence: 66%
“…Caspase-3 is responsible for DNA fragmentation and plays a critical role in apoptosis (McIlwain et al, 2015; Sun et al, 2015). Recently, several researchers have suggested ischemia/reperfusion-induced brain injury might be ameliorated by inhibiting caspase-3 signaling (Wen et al, 2016;Yang et al, 2015a), and in the present study, glycyrrhizinwas found to inhibit increase in caspase-3 and -9 levelscaused by MCAO-induced brain damage (Figure 4).…”
Section: Discussionsupporting
confidence: 66%
“…Relatively loose association of HS with the endothelial glycocalyx likely contributes to the limited protective effect of sevoflurane on the shedding of HS at the beginning of the reperfusion. [11][12][13][14][15][16]18,29 Conversely, Syn-1 has a solid association with the endothelial glycocalyx. As a result, the peak of the Syn-1 release appeared much later during reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous studies have demonstrated that sevoflurane, a volatile anesthetic, can protect various organs or tissues against ischemia-reperfusion injury, including the brain, heart, intestine, and lung, in both humans and laboratory animals. [9][10][11][12][13][14] Furthermore, sevoflurane can preserve the endothelial glycocalyx against ischemia-reperfusion injury in heart tissue. 10 Some studies examined the effects of sevoflurane pretreatment on hepatic tissues following the ischemia-reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, sevoflurane post‐conditioning can significantly improve the long‐term cognitive performance of the rats, increase the number of surviving neurons in cornus ammonis (CA)1 and CA3 hippocampal regions, and protect the histomorphology of the hippocampus (Wen et al . ; Lai et al . ).…”
Section: Discussionmentioning
confidence: 99%